Individual factors affecting compliance with standard infection prevention precautions on the use of personal protective equipment among community health practitioners in Bayelsa State, Nigeria - Dotimi, Doris A.; Odongo, Alfred O.; Atei, Kerochi (International Journal Of Community Medicine And Public Health, 2022)
Background: Individual factors may have an impact on how well healthcare workers adhere to standards for infection prevention. The aim of the study was to identify individual factors affecting compliance with personal protective equipment (PPE) use among community health practitioners in Bayelsa State, Nigeria. Methods: Three hundred and fifty-four (354) self-structured questionnaires were manually distributed among community health practitioners who worked at government-owned primary health care facilities in Bayelsa State, Nigeria. Item mean analysis with a criterion mean set at 2.0 was used to analyze the quantitative data of the 3-Likert scale and results were presented in tables, item mean, and percentages. Results: Individual factors affecting compliance with standard infection prevention precautions on the use of PPE were difficulty to feel veins while wearing PPE (x=2.7), some level of discomfort while performing skills using the PPE (x=2.0), and lack of knowledge of how to use the PPE (x=2.9). It was also revealed that those who complied with the standard infection prevention precaution do so because they understand that the use of PPE prevents them from being infected (x=2.9). Conclusions: Individual factors that affect compliance with standard infection prevention precautions on the use of PPE among community health practitioners can be modified. It is recommended that community health practitioners should have a positive attitude towards compliance with standard infection prevention precautions, especially in this post-COVID-19 era. The government should conduct continuous in-service training and regular supportive supervision on compliance with standard infection prevention precautions among health workers in the primary health care setting.